Study of Beta-Catenin Expression: In Endometrial Hyperplasia and Carcinoma - Sarkar, Sagarika; Sarkar, Ranu; Khandakar, Binny; Maiti, Moumita; Barman, Neepa Manjari; Das, Chandana (Annals of Pathology and Laboratory Medicine, 2018)
Background: Beta-catenin is normally expressed in the membrane and cytoplasm of endometrial glandular cells. Aberrations in beta-catenin expression can predict progression of endometrial hyperplasia to endometrial carcinoma. Nuclear expression of beta-catenin correlates with the increasing histological grade of endometrial cancer. Methods: 51 cases were included in our study. The patients presented with clinical and/or radiological evidence of probable endometrial disease. Formalin fixed paraffin embedded tissues were stained with hematoxylin and eosin followed by histological diagnosis and exact categorisation. Immunostaining with anti-beta-catenin monoclonal antibody carried out on these endometrial biopsies. Result: Statistically significant association was seen between nuclear positivity of beta-catenin in the endometrial glandular cells with increasing severity of endometrial pathology (P < 0.001). Atypical hyperplasia and endometrial carcinoma cases showed nuclear beta-catenin positivity. Nuclear expression of beta-catenin also correlated with advanced FIGO stage of endometrial carcinomas. 67% of endometrial carcinoma of FIGO stage III demonstrated nuclear localization of beta-catenin. A statistically significant association was noted between the intensity of beta-catenin expression and the histological diagnosis (P < 0.001). There was also a statistically significant association between percentage of endometrial glandular cells showing membranous and cytoplasmic positivity and the endometrial pathology (P=0.038). Conclusion: Variations in beta-catenin expression play an important role in endometrial pathology and it is a relatively early event during the endometrial hyperplasia-carcinoma sequence. Alterations in beta-catenin expression in atypical endometrial hyperplasia and in increasing grades of endometrial cancers can be used as a predictive as well as a prognostic indicator.